Drop Out or Self-Exclusion? An Analysis of drop out causes in Mexico's Sonoran High School Students - Elba Abril Valdez; Rosario Román Pérez; María José Cubillas Rodríguez; Icela Moreno Celaya (Universidad Autónoma de Baja California, 2008)
<span style="color: #000000; font-family: Arial, Helvetica, sans-serif; font-size: small; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; background-color: #ffffff; display: inline !important; float: none;">The scholar drop out is not an individual decision. It is conditioned by contextual factors which are identified and analyzed in this research paper among high school students. A survey was applied to 147 high school students to know their family situation, scholar history, reasons why they drop out and their future plans, among other relevant reasons. The results indicated that 86% of the surveyed students abandoned the school between the first and the third semester. Their grade average during the last semester studied was 7.49. The main reasons of the desertion of these students were: economic factors, failure in some subjects, and the lack of interest in their studies. 93% of the participants were not satisfied with the academic level they reached. Nonetheless, they did not plan to resume their studies. The results demonstrated the necessity of an intervention model based on educational policies with higher incentives to add to the school system, flexibility of the transit among subsystems and restructuration of the communication network among the principal actors.